Studi Komparasi Intrusi Air Laut di Dusun Airlouw dan Dusun Erie, Desa Nusaniwe, Kecamatan Nusaniwe, Kota Ambon Berdasarkan Parameter Fisik-Kimia Airtanah - Kololu, Micky (Journal of Science, Technology, and Visual Culture, 2023)
One of the environmental problems often faced by residents in coastal areas is sea water intrusion. The research area is a coastal area so it is very possible for seawater intrusion to occur. This study aimed to determine the hydrogeological system of the research area, and to compare the stretch of intrusion in Airlouw and Erie Village using physical-chemical parameters of groundwater through wells owned by local residents. The research area geology is dominated by Ambon volcanic rocks units, ultramafic rocks and coral limestones. The aquifer system in the study area is an highly to moderately productive aquifers. The lithology that becomes the aquifer is igneous rock in the form of weathering of Ambon volcanic rocks. The results of a comparative study in the research area, based on physical-chemical parameters which include pH, salinity, DHL and TDS values in the: (a) Airlouw Village is characterized as brackish water; whereas (b) Erie Village is characterized as fresh water. Based on the comparison of DO value shows that: (a) Airlouw Village is generally moderately polluted except for SB3 (DO>6.5); whereas (b) Erie Village is not polluted except P6 is moderately polluted (DO:2.0-4.4). Groundwater on: (a) Airlouw Village shows Cl+SO4 facies which indicates of seawater intrusion; whereas (b) Erie Village shows that the Ca-Mg-HCO3 facies has no indicates of seawater intrusion.